Integrating AI-generated videos and the flipped classroom approach to enhance active English language learning - Luz Castillo-Cuesta; Paola Cabrera-Solano; Cesar Ochoa-Cueva (Studies in English Language and Education, 2026)
This study analyzes the use of AI-generated videos and the flipped classroom method to improve active learning in an English as a foreign language (EFL) setting. It aimed to assess the impact of this approach and learners’ perceptions of its effectiveness. The participants in this study were 156 EFL students, aged 20 to 47 years. They were registered in three online courses at a private university in southern Ecuador, and their proficiency level was B2 according to the Common European Framework of Reference for Languages (CEFR). The research employed a quasi-experimental, mixed-methods approach, combining quantitative analysis to evaluate the intervention effects with qualitative insights to explore participants’ experiences and perceptions in depth. The instruments included a diagnostic questionnaire, a pretest, a posttest, a perception survey, and semi-structured interviews. Video content for each course was developed using AI-based tools such as Fliki, Kapwing, Steve AI, InVideo, and Voki, and adapted to specific instructional topics. AI videos, incorporated into the course materials, were reviewed by learners before each synchronous session. The findings revealed that students improved their active learning since scores showed better comprehension and retention of content. The participants asserted that they were exposed to clear explanations, which increased flexibility and encouraged engagement. In addition, AI videos and the flipped classroom approach fostered students’ independent learning. These results underscore the importance of AI technologies for EFL instruction and suggest further research into their sustained impact.